2005
DOI: 10.1515/znc-2005-7-802
|View full text |Cite
|
Sign up to set email alerts
|

Atrovirisidone B, a New Prenylated Depsidone with Cytotoxic Property from the Roots of Garcinia atroviridis

Abstract: A new prenylated depsidone, atrovirisidone B (2), together with naringenin (3) and 3,8″-binaringenin (4) were isolated from the roots of Garcinia atroviridis. Their structures were determined on the basis of spectral data interpretation. Compound 2 showed cytotoxic activity against human breast (MCF-7), human prostate (DU-145) and human lung (H-460) cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Previous studies have reported the isolation of flavonoids such as naringenin, binarigenin, morelloflavone and fukugiside from G. atroviridis . In addition, other phenolic compounds such as xanthone (atroviridin), benzoquinone (atrovirinone), depsidone (atrovirisdone and atrovirisdone B), hydroquinone (4‐methylhydroatrovirinone), cambogin, garcinol, camboginal and isogarcinol were also found in G. atroviridis . The present study found that the polyphenolic compounds in the methanolic extract of G. atroviridis leaves and ripe fruit rind are mostly made up of flavonoids, whereas for the methanol extracts of other parts they are made up of a mixture of flavonoid and non‐flavonoid phenolic compounds.…”
Section: Resultsmentioning
confidence: 50%
“…Previous studies have reported the isolation of flavonoids such as naringenin, binarigenin, morelloflavone and fukugiside from G. atroviridis . In addition, other phenolic compounds such as xanthone (atroviridin), benzoquinone (atrovirinone), depsidone (atrovirisdone and atrovirisdone B), hydroquinone (4‐methylhydroatrovirinone), cambogin, garcinol, camboginal and isogarcinol were also found in G. atroviridis . The present study found that the polyphenolic compounds in the methanolic extract of G. atroviridis leaves and ripe fruit rind are mostly made up of flavonoids, whereas for the methanol extracts of other parts they are made up of a mixture of flavonoid and non‐flavonoid phenolic compounds.…”
Section: Resultsmentioning
confidence: 50%
“…These metabolites were identified by analysing their spectroscopic data and comparing them with the literature data. Compounds (3) and (4) have been isolated previously from G. travancoria [10], while compound (2) from G. atroviridis [11]. Besides, compound (5) has been reported previously from G. cowa [12].…”
Section: Resultsmentioning
confidence: 90%
“…The fruit rind is used in rickets and enlargement of spleen and to heal bone fractures [13]. In Southeast Asian folkloric medicine, a decoction of G. atroviridis (leaves and roots) is sometimes used for the treatment of cough, dandruff, earache, stomach pains associated with pregnancy, and throat irritation [49]. The dried fruit of G. atroviridis is used for improving blood circulation, for the treatment of coughs, as a laxative, and as a expectorant.…”
Section: Uses In Traditional Medical Systemsmentioning
confidence: 99%